The Operational Strategy of the Curriculum Based on Job Characteristics and Its Impact on Labor Market Outcomes - Mostafa Heidari Haratemeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Studies show that graduates of certain occupations earn higher wages when they are placed in the job for which they were trained. Thus, clear evidence for the trade-off between higher earnings returns in certain occupations and the benefit of higher job mobility in lesser occupations is obtained and can be instructive for education policies and the labor market. The present study aims to investigating the effect of job characteristics based on the curriculum on labor market outcomes with three hypotheses in mind and in three separate estimates of the impact of job characteristics on the wage levels of occupational stayers and changers, occupational mobility and unemployment duration was examined.Methodology: A sample of 1,300 graduate workers with a skill set that roughly corresponds to the skill set specified in the latest curriculum was selected.Findings: The results showed workers who have been trained in a particular set of job skills stay in that job and receive higher wages. The higher the nature of a job, the less likely it is that workers will change jobs. For job graduates with a very specific skill set, it is expected that there will be less job mobility. After becoming unemployed, workers from certain jobs need more time to find a new job.Originality/Value: Finally, the research approach can be used to evaluate curricula in all curricula in vocational schools and technical centers that try to prepare people with labor market skills.